2019
DOI: 10.1038/s41368-019-0052-3
|View full text |Cite
|
Sign up to set email alerts
|

Compliant substratum modulates vinculin expression in focal adhesion plaques in skeletal cells

Abstract: The biophysical properties of the extracellular matrix (ECM) dictate tissue-specific cell behaviour. In the skeleton system, bone shows the potential to adapt its architecture and contexture to environmental rigidity via the bone remodelling process, which involves chondrocytes, osteoblasts, osteoclasts, osteocytes and even peripheral bone marrow-derived stem/stromal cells (BMSCs). In the current study, we generated stiff (~1 014 ± 56) kPa, Young’s modulus) and soft (~46 ± 11) kPa silicon-based elastomer polyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Our results presented actin cytoskeleton staining and showed longitudinal filaments along the long axis of the BALB/3T3 cells with colocalization of vinculin on the cell edges. Vinculin is an important FA protein, characteristic for nascent cell-matrix adhesion and mature FA, which bound integrins to cytoplasmic F-actin [ 31 ]. Disruption of the vinculin-F-actin interaction affects cell motility, cell stiffness and adhesion [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results presented actin cytoskeleton staining and showed longitudinal filaments along the long axis of the BALB/3T3 cells with colocalization of vinculin on the cell edges. Vinculin is an important FA protein, characteristic for nascent cell-matrix adhesion and mature FA, which bound integrins to cytoplasmic F-actin [ 31 ]. Disruption of the vinculin-F-actin interaction affects cell motility, cell stiffness and adhesion [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the vinculin-F-actin interaction affects cell motility, cell stiffness and adhesion [ 32 ]. Zhou et al [ 31 ] revealed that vinculin in focal adhesion plaques was significantly decreased in response to soft substrate compared to stiff substrate and cell spreading areas of chondrocytes, osteoblasts, osteoclasts, osteocytes and bone marrow-derived stem cells were also reduced in the soft substrate. Kim and Wirts [ 33 ] characterized parameters of FA of mouse embryonic fibroblasts—MEFs and found that FA display an ellipsoidal shape and FA area was approximately 3 μm 2 for glass substrate and decreased with the decreasing of substrate stiffness, reaching about 1.5 μm 2 on soft gel.…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence staining was performed as previously described. 42 , 43 Briefly, Cells were cultured in Petri dishes specified for confocal laser microscopy for 12 h (1 000 cells per dish, Glass Bottom Cell Culture Dish, Φ15 mm, No. 801002, NEST, Jiangsu, China).…”
Section: Methodsmentioning
confidence: 99%
“… 84 , 85 Based on structural differences, growth plate cartilage has four zones, which are the resting zone, proliferative zone, pre-hypertrophic zone, and hypertrophic zone, and most of the terminally differentiated chondrocytes undergo apoptosis, leaving ECM that is good for the invasion of osteoblasts and blood vessels ( Figure 3 ). 86 , 87 Eventually, osteoblasts secrete bone matrix to replace cartilage matrix and realize ossification. TGF-β2 expresses in all zones during cartilage development, but mainly exists in the ECM of hypertrophy zone.…”
Section: The Basal Role Of Tgf-β2 In Chondrocyte Life Cyclementioning
confidence: 99%